2017
DOI: 10.5433/1679-0359.2017v38n1p125
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy overcoming, temperatures and substrates on germination of Mimosa tenuiflora Willd seeds

Abstract: Mimosa tenuiflora Willd., popularly known as jurema-preta, is an arboreal species of great importance for the brazilian Northeast due to its uses as a medicinal plant and in the restoration of degraded soils. No information is available in the Rules for Seed Analysis and the Instructions for Seed Analysis of Forest Species regarding ideal conditions for of this species. Thus, this study aimed at evaluating the influence of pre-germination treatments, in addition to verifying the germination performance at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
1
0
6
Order By: Relevance
“…Standard germination tests should be conducted for this species. Similar results were reported by Benedito et al (2017), who observed a significant increase in the speed of emergence after manually scarifying seeds of Mimosa tenuiflora Willd.…”
Section: Overcoming Dormancysupporting
confidence: 90%
“…Standard germination tests should be conducted for this species. Similar results were reported by Benedito et al (2017), who observed a significant increase in the speed of emergence after manually scarifying seeds of Mimosa tenuiflora Willd.…”
Section: Overcoming Dormancysupporting
confidence: 90%
“…A unidade experimental foi constituída por saco de polietileno preto, contendo 1,4 kg de areia lavada e autoclavada. As sementes de M. tenuiflora foram coletadas na fazenda experimental Rafael Fernandes, submetidas ao processo de superação de dormência, por meio da imersão em água quente (100 °C por 5 minutos) (Benedito et al 2017), e desinfestação superficial (álcool 70 % e hipoclorito de sódio a 2,5 % por 1 minuto). A semeadura foi realizada com três sementes por saco e, antes da aplicação dos tratamentos, foi feito o desbaste, deixando apenas uma planta por saco.…”
Section: Methodsunclassified
“…A imersão de sementes em água quente é um método que demanda baixo custo, pode ser utilizado em larga escala (CASTRO et al, 2017), proporciona menores riscos de toxidade e é mais prático em relação a métodos químicos e mecânicos de tratamento, especialmente para sementes pequenas (BENEDITO et al, 2017), como é o caso de P. angulata. Levando em consideração a importância medicinal atribuída à essa espécie, além da escassez de estudos sobre seus aspectos de cultivo e germinação, o objetivo foi avaliar a emergência de P. angulata em função da temperatura e tempo de imersão em água.…”
Section: Introductionunclassified